Bernoulli and Euler Polynomials - 24.14 Sums

From testwiki
Revision as of 12:03, 28 June 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
24.14.E1 k = 0 n ( n k ) B k ( x ) B n - k ( y ) = n ( x + y - 1 ) B n - 1 ( x + y ) - ( n - 1 ) B n ( x + y ) superscript subscript 𝑘 0 𝑛 binomial 𝑛 𝑘 Bernoulli-polynomial-B 𝑘 𝑥 Bernoulli-polynomial-B 𝑛 𝑘 𝑦 𝑛 𝑥 𝑦 1 Bernoulli-polynomial-B 𝑛 1 𝑥 𝑦 𝑛 1 Bernoulli-polynomial-B 𝑛 𝑥 𝑦 {\displaystyle{\displaystyle\sum_{k=0}^{n}{n\choose k}B_{k}\left(x\right)B_{n-% k}\left(y\right)=n(x+y-1)B_{n-1}\left(x+y\right)-(n-1)B_{n}\left(x+y\right)}}
\sum_{k=0}^{n}{n\choose k}\BernoullipolyB{k}@{x}\BernoullipolyB{n-k}@{y} = n(x+y-1)\BernoullipolyB{n-1}@{x+y}-(n-1)\BernoullipolyB{n}@{x+y}

sum(binomial(n,k)*bernoulli(k, x)*bernoulli(n - k, y), k = 0..n) = n*(x + y - 1)*bernoulli(n - 1, x + y)-(n - 1)*bernoulli(n, x + y)
Sum[Binomial[n,k]*BernoulliB[k, x]*BernoulliB[n - k, y], {k, 0, n}, GenerateConditions->None] == n*(x + y - 1)*BernoulliB[n - 1, x + y]-(n - 1)*BernoulliB[n, x + y]
Failure Successful Successful [Tested: 54] Successful [Tested: 54]
24.14.E2 k = 0 n ( n k ) B k B n - k = ( 1 - n ) B n - n B n - 1 superscript subscript 𝑘 0 𝑛 binomial 𝑛 𝑘 Bernoulli-number-B 𝑘 Bernoulli-number-B 𝑛 𝑘 1 𝑛 Bernoulli-number-B 𝑛 𝑛 Bernoulli-number-B 𝑛 1 {\displaystyle{\displaystyle\sum_{k=0}^{n}{n\choose k}B_{k}B_{n-k}=(1-n)B_{n}-% nB_{n-1}}}
\sum_{k=0}^{n}{n\choose k}\BernoullinumberB{k}\BernoullinumberB{n-k} = (1-n)\BernoullinumberB{n}-n\BernoullinumberB{n-1}

sum(binomial(n,k)*bernoulli(k)*bernoulli(n - k), k = 0..n) = (1 - n)*bernoulli(n)- n*bernoulli(n - 1)
Sum[Binomial[n,k]*BernoulliB[k]*BernoulliB[n - k], {k, 0, n}, GenerateConditions->None] == (1 - n)*BernoulliB[n]- n*BernoulliB[n - 1]
Failure Failure Successful [Tested: 3] Successful [Tested: 3]
24.14.E3 k = 0 n ( n k ) E k ( h ) E n - k ( x ) = 2 ( E n + 1 ( x + h ) - ( x + h - 1 ) E n ( x + h ) ) superscript subscript 𝑘 0 𝑛 binomial 𝑛 𝑘 Euler-polynomial-E 𝑘 Euler-polynomial-E 𝑛 𝑘 𝑥 2 Euler-polynomial-E 𝑛 1 𝑥 𝑥 1 Euler-polynomial-E 𝑛 𝑥 {\displaystyle{\displaystyle\sum_{k=0}^{n}{n\choose k}E_{k}\left(h\right)E_{n-% k}\left(x\right)=2(E_{n+1}\left(x+h\right)-(x+h-1)E_{n}\left(x+h\right))}}
\sum_{k=0}^{n}{n\choose k}\EulerpolyE{k}@{h}\EulerpolyE{n-k}@{x} = 2(\EulerpolyE{n+1}@{x+h}-(x+h-1)\EulerpolyE{n}@{x+h})

sum(binomial(n,k)*euler(k, h)*euler(n - k, x), k = 0..n) = 2*(euler(n + 1, x + h)-(x + h - 1)*euler(n, x + h))
Sum[Binomial[n,k]*EulerE[k, h]*EulerE[n - k, x], {k, 0, n}, GenerateConditions->None] == 2*(EulerE[n + 1, x + h]-(x + h - 1)*EulerE[n, x + h])
Failure Successful Successful [Tested: 90] Successful [Tested: 90]
24.14.E4 k = 0 n ( n k ) E k E n - k = - 2 n + 1 E n + 1 ( 0 ) superscript subscript 𝑘 0 𝑛 binomial 𝑛 𝑘 Euler-number-E 𝑘 Euler-number-E 𝑛 𝑘 superscript 2 𝑛 1 Euler-polynomial-E 𝑛 1 0 {\displaystyle{\displaystyle\sum_{k=0}^{n}{n\choose k}E_{k}E_{n-k}=-2^{n+1}E_{% n+1}\left(0\right)}}
\sum_{k=0}^{n}{n\choose k}\EulernumberE{k}\EulernumberE{n-k} = -2^{n+1}\EulerpolyE{n+1}@{0}

sum(binomial(n,k)*euler(k)*euler(n - k), k = 0..n) = - (2)^(n + 1)* euler(n + 1, 0)
Sum[Binomial[n,k]*EulerE[k]*EulerE[n - k], {k, 0, n}, GenerateConditions->None] == - (2)^(n + 1)* EulerE[n + 1, 0]
Missing Macro Error Failure Skip - symbolical successful subtest Successful [Tested: 3]
24.14.E4 - 2 n + 1 E n + 1 ( 0 ) = - 2 n + 2 ( 1 - 2 n + 2 ) B n + 2 n + 2 superscript 2 𝑛 1 Euler-polynomial-E 𝑛 1 0 superscript 2 𝑛 2 1 superscript 2 𝑛 2 Bernoulli-number-B 𝑛 2 𝑛 2 {\displaystyle{\displaystyle-2^{n+1}E_{n+1}\left(0\right)=-2^{n+2}(1-2^{n+2})% \frac{B_{n+2}}{n+2}}}
-2^{n+1}\EulerpolyE{n+1}@{0} = -2^{n+2}(1-2^{n+2})\frac{\BernoullinumberB{n+2}}{n+2}

- (2)^(n + 1)* euler(n + 1, 0) = - (2)^(n + 2)*(1 - (2)^(n + 2))*(bernoulli(n + 2))/(n + 2)
- (2)^(n + 1)* EulerE[n + 1, 0] == - (2)^(n + 2)*(1 - (2)^(n + 2))*Divide[BernoulliB[n + 2],n + 2]
Failure Failure Successful [Tested: 3] Successful [Tested: 3]
24.14.E5 k = 0 n ( n k ) E k ( h ) B n - k ( x ) = 2 n B n ( 1 2 ( x + h ) ) superscript subscript 𝑘 0 𝑛 binomial 𝑛 𝑘 Euler-polynomial-E 𝑘 Bernoulli-polynomial-B 𝑛 𝑘 𝑥 superscript 2 𝑛 Bernoulli-polynomial-B 𝑛 1 2 𝑥 {\displaystyle{\displaystyle\sum_{k=0}^{n}{n\choose k}E_{k}\left(h\right)B_{n-% k}\left(x\right)=2^{n}B_{n}\left(\tfrac{1}{2}(x+h)\right)}}
\sum_{k=0}^{n}{n\choose k}\EulerpolyE{k}@{h}\BernoullipolyB{n-k}@{x} = 2^{n}\BernoullipolyB{n}@{\tfrac{1}{2}(x+h)}

sum(binomial(n,k)*euler(k, h)*bernoulli(n - k, x), k = 0..n) = (2)^(n)* bernoulli(n, (1)/(2)*(x + h))
Sum[Binomial[n,k]*EulerE[k, h]*BernoulliB[n - k, x], {k, 0, n}, GenerateConditions->None] == (2)^(n)* BernoulliB[n, Divide[1,2]*(x + h)]
Failure Failure Successful [Tested: 90] Successful [Tested: 90]
24.14.E6 k = 0 n ( n k ) 2 k B k E n - k = 2 ( 1 - 2 n - 1 ) B n - n E n - 1 superscript subscript 𝑘 0 𝑛 binomial 𝑛 𝑘 superscript 2 𝑘 Bernoulli-number-B 𝑘 Euler-number-E 𝑛 𝑘 2 1 superscript 2 𝑛 1 Bernoulli-number-B 𝑛 𝑛 Euler-number-E 𝑛 1 {\displaystyle{\displaystyle\sum_{k=0}^{n}{n\choose k}2^{k}B_{k}E_{n-k}=2(1-2^% {n-1})B_{n}-nE_{n-1}}}
\sum_{k=0}^{n}{n\choose k}2^{k}\BernoullinumberB{k}\EulernumberE{n-k} = 2(1-2^{n-1})\BernoullinumberB{n}-n\EulernumberE{n-1}

sum(binomial(n,k)*(2)^(k)* bernoulli(k)*euler(n - k), k = 0..n) = 2*(1 - (2)^(n - 1))*bernoulli(n)- n*euler(n - 1)
Sum[Binomial[n,k]*(2)^(k)* BernoulliB[k]*EulerE[n - k], {k, 0, n}, GenerateConditions->None] == 2*(1 - (2)^(n - 1))*BernoulliB[n]- n*EulerE[n - 1]
Missing Macro Error Failure - Successful [Tested: 3]
24.14.E7 j = 0 m k = 0 n ( m j ) ( n k ) B j B k m + n - j - k + 1 = ( - 1 ) m - 1 m ! n ! ( m + n ) ! B m + n superscript subscript 𝑗 0 𝑚 superscript subscript 𝑘 0 𝑛 binomial 𝑚 𝑗 binomial 𝑛 𝑘 Bernoulli-number-B 𝑗 Bernoulli-number-B 𝑘 𝑚 𝑛 𝑗 𝑘 1 superscript 1 𝑚 1 𝑚 𝑛 𝑚 𝑛 Bernoulli-number-B 𝑚 𝑛 {\displaystyle{\displaystyle\sum_{j=0}^{m}\sum_{k=0}^{n}\genfrac{(}{)}{0.0pt}{% }{m}{j}\genfrac{(}{)}{0.0pt}{}{n}{k}\frac{B_{j}B_{k}}{m+n-j-k+1}=(-1)^{m-1}% \frac{m!n!}{(m+n)!}B_{m+n}}}
\sum_{j=0}^{m}\sum_{k=0}^{n}\binom{m}{j}\binom{n}{k}\frac{\BernoullinumberB{j}\BernoullinumberB{k}}{m+n-j-k+1} = (-1)^{m-1}\frac{m!n!}{(m+n)!}\BernoullinumberB{m+n}

sum(sum(binomial(m,j)*binomial(n,k)*(bernoulli(j)*bernoulli(k))/(m + n - j - k + 1), k = 0..n), j = 0..m) = (- 1)^(m - 1)*(factorial(m)*factorial(n))/(factorial(m + n))*bernoulli(m + n)
Sum[Sum[Binomial[m,j]*Binomial[n,k]*Divide[BernoulliB[j]*BernoulliB[k],m + n - j - k + 1], {k, 0, n}, GenerateConditions->None], {j, 0, m}, GenerateConditions->None] == (- 1)^(m - 1)*Divide[(m)!*(n)!,(m + n)!]*BernoulliB[m + n]
Failure Failure Successful [Tested: 9] Successful [Tested: 9]